Optimalisasi Kualitas Air pada Tambak Udang Vannamei Menggunakan Modul IoT - Agus Indra Gunawan; Setiawardhana Setiawardhana; M Wisnu Gunawan; Daffa Syah Alam; Zaikhul Sulthon Suasono; Silfiana Nur Hamida (GUYUB: Journal of Community Engagement, 2025)
Indonesian has great potential in the fisheries sector, with vaname shrimp as a leading commodity due to its competitive price and efficient cultivation. However, many shrimp farmers in Keputih Village, Surabaya City still lack an understanding of the importance of monitoring and managing pond water quality. In response to this, the Master of Applied Electrical Engineering and Master of Applied Informatics and Computer Engineering teams at Politeknik Elektronika Negeri Surabaya (PENS) introduced an IoT-based Water Quality Meter module. This program not only provides real-time water quality monitoring technology that can be accessed via smartphone or laptop, but also provides training and assistance to pond farmers in adopting this technology. Evaluation results show that pond farmers can operate the module well to monitor water quality parameters, making it easier to monitor ponds accurately and practically. The community service program is expected to increase yields, strengthen collaboration between academics and communities, and encourage the adoption of modern technology in shrimp farming.